Brassinosteroid signal transduction: still casting the actors - Schumacher, Karin; Chory, Joanne (Current opinion in plant biology, 2000)
Significant advances in the genetic dissection of brassinosteroid biosynthesis and signaling have been made during the past few years. Genetic and biochemical data have helped to elucidate the pathways of biosynthesis of brassinolide, the most active brassinosteroid. In addition, several models have been put forward for the perception of brassinolide by its putative receptor, BRI1, a ubiquitously expressed plasma membrane localized protein kinase. These studies provide the basic framework for future analysis of brassinosteroid signaling.
Gesehen am 07.10.2021